Morningness-eveningness and anxiety trait among adolescents. - Díaz-Morales, Juan F.; Collado-Mateo, María J.; Escribano, Cristina; Delgado, Pedro (Anales de Psicología / Annals of Psychology, 2013)
The relationship between morningness-eveningness and anxiety trait among adolescents was studied. Six hundred thirty eight adolescents between 12 and 14 years old participated in this study. Morningness-eveningness was measured by the Morningness-Eveningness Scale for Children, MESC (Carskadon, Vieira & Acebo, 1993) and anxiety trait was measured by the State-Trait Anxiety Inventory for Children, STAIC (Spielberger, Edwards, Lushene, Montuori & Platzek, 1973; Spielberger, Edwards & Lushene, 1990). Results showed higher eveningness among girls, eveningness increased with age and anxiety trait was higher as morningness diminished. Therefore, evening-oriented adolescents claimed higher anxiety trait, which was waited since they would have a greater misalignment between both biological and social rhythms (school morning schedules).